Purification and Characterization of Four New Cysteine Endopeptidases From Fruits of Bromelia pinguin L. Grown in Cuba - Abreu Payrol, Juan (2008)
Bromelia pinguin L. is a plant broadly distributed in Central America and Caribbean islands. The fruits have been used in traditional medicine as anthelmintic, probably owed to the presence of a mixture of cysteine endopeptidases, initially termed pinguinain. This work deals with the purification and characterization of the four main components of that mixture, two of them showing acid pI and the other two alkaline pI. Molecular masses (SDS-PAGE and MALDI-TOF), N-terminal sequence and the reactivity and kinetic parameters versus synthetic substrates (p-nitrophenyl-N-α-CBZ-amino acid esters, PFLNA, Z-Arg-Arg-p-NA, and Z-Phe-Arg-p-NA) of the studied peptidases are given, as well as the N-terminal sequences of the enzymes and the homology degree with other plant endopeptidases.